PSYCHOLOGICAL CONTRACT AND EMPLOYEE RETENTION: EVIDENCE FROM UYI GRAND HOTEL, BENIN CITY, EDO STATE - OBAKPOLOR, Idemudia Ernest (Annals of Spiru Haret University. Economic Series, 2020)
Abstract The breach of psychological contract often results in a decline in employees’ willingness to contribute to and intention to stay in an organization and, employee turnover is an endemic issue in hospitality industry worldwide. Psychological contract and employee retention has been subjects of discourse among social and management scientists form a wide range of disciplines in the last two decades. But unfortunately, very insufficient number of studies in these areas has been conducted in Nigeria and none has been carried out in hospitality industry. This study was undertaken to fill this obvious research gap. A descriptive method was adopted and data was collected via a survey of 53 respondents. Data collected were analyzed using correlation and linear regression analysis with the aid of Statistical Package for Social Sciences (SPSS) version 21. The results of the study showed that there is a significant relationship between psychological contract and employee retention. The study also revealed that psychological contract; positively and significantly influence employee retention in Uyi Grand Hotel, Benin City, Edo State. Requisite conclusion and recommendations were provided in the light of theoretical and empirical findings.